Decision making processes in people with symptoms of acute myocardial infarction: qualitative study - Pattenden, Jill (BMJ, 2002)
OBJECTIVE: To identify the themes that influence decision making processes used by patients with symptoms of acute myocardial infarction. DESIGN: Qualitative study using semistructured interviews. SETTING: Two district hospitals in North Yorkshire. PARTICIPANTS: 22 patients admitted to hospital with confirmed second, third, or fourth acute myocardial infarction. MAIN OUTCOME MEASURE: Patients' perceptions of their experience between the onset of symptoms and the decision to seek medical help. RESULTS: Six main themes that influence the decision making process were identified: appraisal of symptoms, perceived risk, previous experience, psychological and emotional factors, use of the NHS, and context of the event. CONCLUSIONS: Knowledge of symptoms may not be enough to promote prompt action in the event of an acute myocardial infarction. Cognitive and emotional processes, individual beliefs and values, and the influence of the context of the event should also be considered in individual interventions designed to reduce delay in the event of symptoms of acute myocardial infarction.